Crowdlending for German SMEs - von Westphalen, Nicolas Clemens Maria Graf (2020)
Fintech is revolutionizing the financial world. And concurrently with this phenomenon, there emerges a business model that owes its novel growth above all to the rigidity of banks and new regulatory requirements since the financial crisis of 2008: Crowdlending for SMEs. In Germany, however, the new solution, which connects lenders and borrowers directly via a platform, still has start-up difficulties. Based on this, the goal of this research is to examine factors that determine the decision to adopt Crowdlending among German SMEs. Using the innovation adoption framework by Wisdom, et al. (2013), a qualitative research design is conducted to compare two groups of enterprises according to their per-ception towards the emerging financing solution. Every group consists of six participants and is created according to category, industry and the decision of having already adopted Crowdlending or not, resulting in a sample size of twelve interviewees. The study shows that although facing trust issues, factors, such as speed, low complexity and the possibility of rising awareness among SME’s customers are crucial for an adoption decision. On a company level, innovative management, the readiness to change and curiosity signifi-cantly yield a positive effect on the decision to adopt. The tendency appears to be even stronger, when the firm has recently faced a change in leadership from an older to a younger entrepreneur. While theoretically contributing to the scarce literature about Crowdlending in combination with German SMEs, it gives thought impacts to involved stakeholders.